2006
DOI: 10.1021/bi0608717
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-Mediated Phospholipidation of Plasma Lipoproteins Increases HDL Cholesterophilicity and Cholesterol Efflux via SR-BI

Abstract: Cellular cholesterol efflux is an early, obligatory step in reverse cholesterol transport, the putative antiatherogenic mechanism by which human plasma high density lipoproteins (HDL) transport cholesterol from peripheral tissue to the liver for recycling or disposal. HDL-phospholipid content is the essential cholesterol-binding component of lipoproteins and therefore a major determinant of cholesterol efflux. Thus, increased phospholipidation of lipoproteins, particularly HDL, is one strategy for increasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
2
19
0
5
Order By: Relevance
“…4B, C) and thereby provides a mechanism for removing excess surface material from the fused particles. Thus, different modes of VLDL perturbation (such as lipase-mediated TG hydrolysis or heatinduced VLDL fusion) may lead to transient formation of similar apoE-containing HDL-like particles.Earlier studies of HDL and LDL have shown that thermal and solute-induced perturbations may mimic aspects of enzymatic lipoprotein remodeling such as particle fusion, apolipoprotein dissociation and phospholipid transfer (10,11,36,37). The results reported here extend this notion to VLDL and suggest that thermal perturbation of VLDL mimics aspects of protein and lipid transfer among TG-rich lipoproteins and HDL pools in plasma.…”
supporting
confidence: 74%
“…4B, C) and thereby provides a mechanism for removing excess surface material from the fused particles. Thus, different modes of VLDL perturbation (such as lipase-mediated TG hydrolysis or heatinduced VLDL fusion) may lead to transient formation of similar apoE-containing HDL-like particles.Earlier studies of HDL and LDL have shown that thermal and solute-induced perturbations may mimic aspects of enzymatic lipoprotein remodeling such as particle fusion, apolipoprotein dissociation and phospholipid transfer (10,11,36,37). The results reported here extend this notion to VLDL and suggest that thermal perturbation of VLDL mimics aspects of protein and lipid transfer among TG-rich lipoproteins and HDL pools in plasma.…”
supporting
confidence: 74%
“…A different approach, involving the phospholipid enrichment of HDL, has also been described but has only been tested in vitro [107]. During this treatment, HDL is incubated in the presence of phospholipid vesicles along with cholate, which are later removed by dialysis.…”
Section: Hdl-replacement Agentsmentioning
confidence: 99%
“…17,18 This suggests that the potency of liposomes to mobilize tissue cholesterol or to regress atherosclerotic lesions in vivo could be influenced by the degree of solubilization of the basic vesicular structure of the liposomes by HDL and other plasma components. The findings reported here suggest that DMPC liposomes behave in a manner similar to egg or soy PC liposomes.…”
Section: Discussionmentioning
confidence: 99%